Comparison of psychosocial strengths and difficulties in children born through assisted reproductive technology versus naturally conceived children - Kamal, A. H. M. Kazi Mostofa; Bhuiyan, Shah M. A. Uddin; Laila, Luna; Inamul Islam, M.; K. Biswas, Anup (International Journal of Research in Medical Sciences, 2024)
Background: Assisted reproductive technology (ART) is a set of medical interventions used to facilitate the conception process in couples suffering from fertility issues. ART encompasses several techniques, including ovulation induction (OI), artificial insemination, testicular sperm extraction (TESE), in vitro fertilization (IVF), and intracytoplasmic sperm injection (ICSI). This current study aimed to analyze the correlation between psychological strength and difficulties among children born by ART and normally conceived (NC) children. Methods: The study was conducted in a longitudinal retrospective fashion, in Combined Military Hospital, Dhaka, Bangladesh, from December 2022 to June 2023. A total of 47 participants from the ART group and 50 participants from the NC group were selected as study subjects by purposive sampling technique. Data were gathered using a pre-designed questionnaire and analyzed using the statistical package for the social sciences (SPSS) version 23.0 computer program. Results: The age range of the study participants was between 2 to 4 years old. A majority of the participants were female (53.2%), hailed from middle-class families (59.6%), lived in urban settings (42.6%), and identified as Muslim (72.3%). In terms of illnesses, a small proportion experienced physical ailments (6.4%) and psychiatric conditions (10.6%). Conclusions: Despite persistent worries regarding the potential adverse developmental effects on children conceived by ART, research findings suggest that such children do not exhibit noteworthy physical, psychological, or developmental challenges when compared to those conceived naturally.